A Narrative Exploring the Potential of ChatGPT: How AI Models Are Changing the Way We Interact with Technology - Eka, Muhammad; Asih, Munjiat Setiani; Damayanti, Fera; Saragih, Rusmin; Supiyandi, Supiyandi (Journal of Computer Science, Artificial Intelligence and Communications, 2024)
This study explores the perceptions, attitudes, and ethical considerations surrounding the use of ChatGPT among university students. By combining quantitative and qualitative research methods, including surveys and a review of existing literature, the study examines how ChatGPT is utilized in academic settings and its impact on learning outcomes, academic integrity, and scholarly achievements. The findings suggest that ChatGPT significantly enhances students' productivity, learning experiences, and writing abilities. However, concerns regarding its potential misuse, particularly about academic integrity, plagiarism, and over-reliance on AI tools, were also identified. The research highlights the importance of establishing clear ethical guidelines and policies to regulate the use of AI in educational settings. Future research should focus on the long-term effects of ChatGPT on students' academic development and investigate strategies for promoting responsible AI usage in higher education.